Spectrum of Chronic Renal Failure in Children at Dr. Cipto Mangunkusumo Hospital, Jakarta - Tambunan, Taralan; Wirya, I.G.N. Wila; Alatas, Husein (Paediatrica Indonesiana, 1990)
The aim of this paper is to report the hospital prevalence of chronic renal failure, the spectrum of the various underlying diseases and the outcome of these patients managed with conservative treatment. The diagnosis of chronic renal failure was established either on the first hospital admission or during the course of the disease. During the period of three years (1986-1988), 489 cases of various renal diseases were admitted to the Dr. Cipto Mangunkusumo Hospital in Jakarta. Twenty-one cases (4.3%) with chronic renal failure were diagnosed and in 18 out of them (85.7%) the underlying diseases could be established while in the remaining three cases (14.3%) the primary renal diseases were uncertain. All patients were managed conservatively and none of them were treated either by regular dialysis or renal transplantation. Eight patients (38.0%) died during follow up, another five cases (23.8%) were still under routine control, while the remaining eight (38.0%) were lost on follow up.